Internationalization, competitiveness enhancement and export performance of emerging market firms: Evidence from Vietnam - Ha Thi Van Pham (Copenhagen Business School (CBS), 2009)
The thesis revolves around the internationalization of Vietnamese firms - that is, how the international competitiveness of these firms is enhanced in terms of both upstream and downstream value chain activities and the export performance implications hereof. For Vietnamese firms, as well as for other firms from emerging markets, internationalization trajectories may differ considerably from the internationalization patterns portrayed in classical theories (such as the Uppsala Model) based on observations of the internationalization of firms from Western, developed market economies. Classical theories have primarily focused on firms' marketing & sales and networking capabilities as levers of internationalization – and less on upstream capabilities, such as manufacturing and auxiliary service competencies. Likewise the situation in other emerging markets many Vietnamese firms are inserted in global value chains (GVCs) governed by multinational buyers. For these firms, manufacturing skills may be of equal - or greater - importance to export performance than the mastering of marketing & sales and networking in foreign markets. The thesis presents various theoretical perspectives on firms' internationalization – perspectives that vary in terms of their focus on either upstream or downstream activities (or, the interrelationship of these two types of activities). The thesis tries to fill out the knowledge gap as to which of these theoretical perspectives fit best the trajectories of Vietnamese manufacturing firms involved in exports. In doing so, the thesis also draws on GVC models, entrepreneurial literature, and studies of economic as well as strategic export performance. Unique survey data covering 226 Vietnamese manufacturers involved in exporting was collected through face-to-face interviews conducted in Hanoi and Ho Chi Minh City. On the basis of these data a set of hypotheses is tested using structural equation modelling as a statistical tool. The empirical study suggests that Vietnamese firms create international competitiveness in relation to both upstream and downstream activities. Furthermore, the study suggests that upstream competitiveness of the sample firms is significantly more attractive in terms of economic export performance (export sales, profitability and growth) than downstream competitiveness. However, when export performance is measured in more far-sighted, strategic terms, there are no significant differences between the two dimensions of competitiveness. The study also reveals some interesting industry differences: for firms in the “low-tech” textiles & garments industry, upstream competitiveness has greater impact on economic export performance than downstream competitiveness. Conversely, downstream competitiveness results in a higher economic return than upstream competitiveness for firms from the “high-tech” industries of electronics and mechanical manufactures In the last part of the thesis, theoretical, empirical, and managerial implications are discussed along with conclusions and suggestions for future research.
hdl:10398/7934
Keywords: 650